Transorbital Endoscopic Surgery for Sphenoid Wing Meningioma: Long-term Outcomes & Surgical Technique - Goncalves, Nicholas (Division of Otorhinolaryngology, 2020)
Sphenoid wing meningiomas are benign tumors that result in proptosis, visual impairment and pain. Traditional open surgical approaches are associated with significant morbidity. Transorbital endoscopic surgery has been developed as a minimally invasive approach to gain access to these tumors and address the main presenting symptoms. The aim of the study was to assess long term vision and proptosis outcomes in patients undergoing a transorbital endoscopic resection of sphenoid wing meningioma using a combined endonasal, precaruncular and extended superior eyelid approach and to describe the surgical approach. Materials & Methods A retrospective chart review was conducted in 21 patients with lateral sphenoid wing meningioma at Groote Schuur Hospital & Cape Town Mediclinic from 2015–2019. All patients had undergone a transorbital endoscopic subtotal resection (Simpson grade II – IV) by the same surgical team. Vision was assessed using a Snellen chart and proptosis measured in mm using a Hertel exophthalmometer by an ophthalmologist. Measurements were taken at 6 weeks, 6 months and at 1 year postoperatively and compared to pre-operative values. Patients were categorized according to the WHO classification of vision into group A (blind), group B (low vision) & group C (normal vision) according to their pre-operative visual acuity. Nonparametric statistical tests employing the Wilcoxon Signed-Ranks Test were used for analysis. Statistical significance was determined by a confidence interval of 0.95, p = < 0.05 for both visual acuity (converted to LogMar) and proptosis in mm. Results A total of 21 patient charts were reviewed. The mean age of presentation was 48.8 years (range 34-79 years), and the majority of patients were female (20/21 = 95%). The most common presenting complaints were loss of vision (100%), proptosis (95%) and headache (76%). Preoperative visual results were as follows: 10 (48%) in group A (blind), 4 (19%) in group B (low vision) and 7 (33%) in group C (normal vision). In group A, 6 (60%) remained unchanged, 2 (20%) deteriorated & 1 (10%) improved. In group B, 3 (75%) improved, and 1 (25%) remained stable. In group C, 5 (71%) improved and 2 (29%) remained stable. Vision in groups B & C showed no deterioration. Patients in group A showed no benefit from optic nerve decompression. Vision in groups B & C showed a statistically significant improvement at 6 weeks [95% CI] (p = 0.021). This trend extended to long term follow up at 6 months [95% CI] (p= 0.021) and 1 year [95% CI] (p = 0.0054) postoperatively. Proptosis initially decreased, proving statistical significance at 6 weeks [95% CI] (p = 0.0054) postoperatively. The decrease at 6 months (p = 0.08) was not statistically significant and trended towards an increase in proptosis by 1 year (p = 0.78) postoperatively. The mean hospital stay was 2.7 days (range 2 – 4 days). The majority of tumors were histologically classified as WHO grade I. Conclusion Endoscopic medial optic canal decompression prior to transorbital multiportal surgery for sphenoid wing meningioma stabilizes or improves visual acuity for at least 1 year. Lateral orbitotomy via a superior eyelid approach and subtotal tumor resection initially decreases proptosis, but in the long term, returns to its preoperative state by 1 year if the main tumor component is not addressed. The earlier that medial optic nerve decompression is performed and the better the preoperative visual acuity, the greater the likelihood of favorable long-term visual outcomes.